2022
DOI: 10.1262/jrd.2021-088
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition and bi- and multi-nucleated trophoblast cell formation in ovine conceptuses during the peri-implantation period

Abstract: Epithelial-mesenchymal transition (EMT), which is common in cancer metastasis, is also observed during developmental processes such as embryo implantation into the maternal endometrium in humans and rodents. However, this process has not been well characterized in the non-invasive type of implantation that occurs in ruminants. To understand whether EMT occurs in ruminant ungulates, ovine conceptuses (embryo plus extraembryonic membranes) from days 15 (P15: pre-attachment), 17 (P17: during attachment), and 21 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Seo and coworkers provided evidence that ovine trophectodermal cells went through homotypic cell fusion, not heterotypic, and formed syncytiotrophoblast-like fused cells [ 55 ]. This observation agrees with our recent publication in which bi-nucleated and multi-nucleated cells observed in vivo are all homotypic cell fusions [ 56 ].…”
Section: Cells Gain Their Mobility Through Epithelial-mesenchymal Tra...supporting
confidence: 93%
See 1 more Smart Citation
“…Seo and coworkers provided evidence that ovine trophectodermal cells went through homotypic cell fusion, not heterotypic, and formed syncytiotrophoblast-like fused cells [ 55 ]. This observation agrees with our recent publication in which bi-nucleated and multi-nucleated cells observed in vivo are all homotypic cell fusions [ 56 ].…”
Section: Cells Gain Their Mobility Through Epithelial-mesenchymal Tra...supporting
confidence: 93%
“…In the ruminants, including Bovidae, syncytiotrophoblast cells are not formed; rather, trinucleate cells, resulting from the fusion between binucleate trophoblast cells and maternal epithelial cell often appear in the uterine stroma [ 64 ]. Recently, we [ 56 ] and others [ 55 ] demonstrated that binucleate and/or multi-nucleate trophoblast cells are derived from the fusion of trophoblast cells. In animals with epitheliochorial placentation, such as horses, camels, pigs, hippopotamuses, and cetaceans, the syncytiotrophoblast layer is not formed; however, binucleate trophoblast cells are found in the horse placenta.…”
Section: Formation Of Syncytiotrophoblast Layer In the Mammalian Speciesmentioning
confidence: 99%
“…The results of this experiment revealed that the expression of genes expressing immunoglobulin adhesion molecules, such as L1CAM , LAMC2 , and LAMA5 , was significantly lower in EH horn buds compared to WH ( Table S1 ), suggesting that EMT was inhibited in EH horn buds, which may lead to failure of neural crest cell migration initiation. Similarly, the top 20 Hub proteins from the protein interaction analysis also screened for multiple proteins associated with cell adhesion, such as cadherin 1 (CDH1), integrin subunit beta 2 (ITGB2) and integrin subunit beta 3 (ITGB3) were involved in the biological process of the regulation of cell adhesion molecule in these results [ 26 , 27 , 28 ]. It suggested that the Pc locus may inhibit EMT in neural crest cells by regulating the expression of cell adhesion molecules, particularly E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been believed that the BNCs fuse with endometrial cells on the surface of the placenta on the maternal side, which invade the endometria and transport hormones to the mother, thereby maintaining pregnancy [58]. It was recently shown by two laboratories that the fusion between trophoblast cells in sheep is not limited to the formation of BNCs, and new BNCs involve the lateral fusion between growing syncytial plaques [61,62].…”
Section: Morphology Of the Bovine Placentamentioning
confidence: 99%
“…It is possible that BERV-K1 became a key player in bovine placentation (Table 2). Interestingly, BERV-K1 also played a role in the formation of trophoblast hybrid cells in heterologous trophoblast cells (sheep trophoblast cells) [62]. In addition to Syncytin-Rum1 and BERV-K1, other ERV envs such as BERV-K2 [49], bERVE-A [50], and bERVE-B [50] have been identified.…”
Section: Figurementioning
confidence: 99%